A Children's Book About Lying - Berry, Joy Wilt.; Costanza, John (Chicago : Childrens Press, 1985)
Explains to children the differences between lying and telling a story for entertainment. Also explains why it is better not to lie.
3.8
K-3
Keywords: Truthfulness and falsehood -- Juvenile literature; Honesty; Truthfulness and falsehood